Modern educational conditions of distance learning to the professional training of students with an english-language form of study in the specialty "obstetrics and gynaecology" - Kurunthodi, Ch.; Braji, A. (Запорізький державний медико-фармацевтичний університет, 2024)
Aim of the study: Academic mobility online allows students in the specialty "Obstetrics and Gynecology" to gain experience from leading specialists of the department, who are ready to share modern knowledge and rules for mastering practical skills. This experience helps students deepen their competencies and more easily adapt to the complex challenges that have arisen in our modern world, against the backdrop of war.
Keywords: тези доповідей